The Implementation Of Merdeka Curriculum For Formal English Learning - Iffa Kharimah; Siminto; Zaitun Qamariah (Universitas Palangka Raya, 2023)
This article aims to explain The Implementation Of Merdeka Curriculum For Formal English Learning. The curriculum becomes very important in educational institutions because the curriculum is the “heart” of education. This study uses a descriptive qualitative approach with library research methods, using synthesis and content analysis. The results of the study show that the Implementation of the Merdeka Curriculum at the Elementary School level prioritizes project-based learning. In the implementation of learning is not only focused on the world of knowledge but emphasizes the mastery of character, literacy, skills, and technology. Implementation of the Merdeka Curriculum in English Learning at the Middle School Level, namely by applying the Project Based Learning method is the application of student-oriented learning (student-centered). Implementation of the Merdeka Curriculum at the English Learning High School level is by implementing a curriculum that is Basic Framework, Targeted Competency, Curriculum Structure, Learning Process, Assessment, Teaching Resources, and Curriculum Tools.